Human Rights And Public Policy Implementation : Narcotics - Riza Amalia (Journal Of Global Research Publications, 2024)
This research discusses the relationship between Human Rights (HAM) and the implementation of public policies related to narcotics. In a global context, narcotics policies are often a source of controversy due to their impact on individual rights. This research evaluates how narcotics policies can affect basic rights such as the rights to life, liberty, health and justice. In some cases, harsh legal crackdowns on narcotics have led to human rights violations, such as arbitrary arrest and detention, as well as the use of force by security forces. On the other hand, some countries have tried alternative approaches, including decriminalization or legalization of narcotics, with the aim of reducing the negative impact on individuals. This research uses a normative approach. The conclusion from this research is that it is important to maintain a balance between efforts to prevent and handle narcotics with protecting individual human rights. Effective implementation of narcotics policies must take into account the basic rights of individuals and seek to reduce negative social impacts. This research underlines the need for a holistic and sustainable approach in dealing with narcotics issues without compromising human rights